Expanding insurance coverage for in vitro fertilisation with preimplantation genetic testing: putting the cart before the horse - Lisi, Emily C. (Journal of medical ethics, 2022)
Madison Kilbride recently argued that insurance (eg, Centers for Medicare & Medicaid Services (CMS)) should cover in vitro fertilisation with preimplantation genetic testing (IVF-PGT) services for couples at high risk of having a child affected with a genetic condition. She argues that IVF-PGT meets CMS’s definition of ‘medically necessary care’, where such care includes ‘services or supplies needed to diagnose or treat an illness, injury, condition, disease or its symptoms’. Kilbride argues that IVF-PGT satisfies this definition in two ways: as a diagnostic tool and as a treatment. Contradicting Kilbride, however, I argue that IVF-PGT provides neither diagnosis nor treatment under CMS’s definition. Thus, as long as we accept CMS’s definition of medically necessary care—which Kilbride does, explicitly—it follows that IVF-PGT does not count as medically necessary care. Still, there may be other reasons to conclude that IVF-Preimplantation genetic testing should be covered, and so, it would be a mistake to reject Kilbride’s conclusion altogether. The problem is simply that Kilbride’s argument—that the procedure should be covered because it is medically necessary per CMS’s definition—is not sound. I conclude by discussing a number of other genetic services that are not currently being covered despite the fact that (unlike IVF-PGT) they do seem to satisfy CMS’s definition of ‘medically necessary diagnosis or treatment’. These services, I argue, should be provided under CMS before we consider expanding coverage to include elective procedures such as IVF-PGT.